2015
DOI: 10.4172/2157-7048.1000245
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Entrainment and Transport of Gas Bubbles by a Vortex Ring

Abstract: The control of the motion of small gas bubbles by a vortex ring is explored through numerical simulation. Hydrogen bubbles with a diameter of 0.2 mm are arranged in quiescent water, forming a bubble cluster. A vortex ring is launched vertically, passing through the bubble cluster. The behaviors of the vortex ring and bubble motion are analyzed. The diameter of the vortex ring at launch is 42.5 mm, and the bubble volume fraction is less than 0.04. As the vortex ring convects through the bubble cluster, it displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
(22 reference statements)
1
8
0
Order By: Relevance
“…Therefore, the interaction between a vortical flow and light particles cannot be inferred from the results with heavy particles. Uchiyama and Yoshii (2015) numerically simulated the entrainment and transport of the gas bubbles by a vortex ring at Re Γ = 400, 500 and 600. The total volume of the entrained bubbles in the vortex core is higher for lower values of Re Γ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the interaction between a vortical flow and light particles cannot be inferred from the results with heavy particles. Uchiyama and Yoshii (2015) numerically simulated the entrainment and transport of the gas bubbles by a vortex ring at Re Γ = 400, 500 and 600. The total volume of the entrained bubbles in the vortex core is higher for lower values of Re Γ .…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, the methods used to solve for the liquid phase are called semi-Lagrangian, hybrid-Eulerian–Lagrangian, or vortex-in-cell methods. Examples of investigations related to the semi-L–L approach are Nguyen et al (2019), Wang et al (2013) and Uchiyama and Yoshii (2015) and Uchiyama et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Research on such interactions has scarcely been reported except for the studies of Sridhar and Katz [6], [7] and Higuera [8], which investigated the motion of a single bubble in a vortex core and the bubble-induced deformation of a vortex ring. Thus, the current authors [9][10][11][12] researched possible entrainment and transport of small bubbles by a vortex ring. Uchiyama [9] conducted a numerical simulation of a water jet laden with small air bubbles and showed that a vortex ring induced near the nozzle outlet by an axisymmetric disturbance involves the bubbles and convects with the bubbles along the jet centerline.…”
Section: Introductionmentioning
confidence: 99%
“…Uchiyama [9] conducted a numerical simulation of a water jet laden with small air bubbles and showed that a vortex ring induced near the nozzle outlet by an axisymmetric disturbance involves the bubbles and convects with the bubbles along the jet centerline. Uchiyama and Yoshii [10] simulated the bubble motion and the behavior of a vortex ring launched toward a bubble cluster, and they demonstrated the entrainment and transport of the bubbles by the vortex ring as well as the change in the strength of the vortex ring because of the entrained bubbles. Wang et al [11] simulated the interaction between a bubble plume and a vortex ring and reported the effect of the bubbles on the behavior of the vortex ring.…”
Section: Introductionmentioning
confidence: 99%
“…Uchiyama [1] conducted a numerical simulation of a water jet laden with small air bubbles and showed that a vortex ring, induced near the nozzle outlet by an axisymmetric disturbance, incorporates the bubbles and convects with them along the jet centerline. Uchiyama and Yoshii [2] simulated the bubble motion and behavior of a vortex ring launched toward a bubble cluster. Their simulation found that the bubbles are entrained and transported by the vortex ring and that the strength of the vortex ring is affected by the entrained bubbles.…”
Section: Introductionmentioning
confidence: 99%